Glycosylated Nanoparticles for Cancer-Targeted Drug Delivery - Torres-Pérez, Sergio Andrés; Torres-Pérez, Cindy Estefani; Pedraza-Escalona, Martha; Pérez-Tapia, Sonia Mayra; Ramón-Gallegos, Eva (Frontiers in Oncology, 2020)
Nanoparticles (NPs) are novel platforms that can carry both cancer-targeting molecules and drugs to avoid severe side effects due to nonspecific drug delivery in standard chemotherapy treatments. Cancer cells are characterized by abnormal membranes, metabolic changes, the presence of lectin receptors, glucose transporters (GLUT) overexpression, and glycosylation of immune receptors of programmed death on cell surfaces. These characteristics have led to the development of several strategies for cancer therapy, including a large number of carbohydrate-modified NPs, which have become desirable for use in cell-selective drug delivery systems because they increase nanoparticle-cell interactions and uptake of carried drugs. Currently, the potential of NP glycosylation to enhance the safety and efficacy of carried therapeutic antitumor agents has been widely acknowledged, and much information is accumulating in this field. This review seeks to highlight recent advances in NP stabilization, toxicity reduction, and pharmacokinetic improvement and the promising potential of NP glycosylation from the perspective of molecular mechanisms described for drug delivery systems for cancer therapy. From preclinical proof-of-concept to demonstration of therapeutic value in the clinic, the challenges and opportunities presented by glycosylated NPs, with a focus on their applicability in the development of nanodrugs, are discussed in this review.